Wind Power Potential Assessment at Different Locations in Lebanon: Best–Fit Probability Distribution Model and Techno-Economic Feasibility - Kassem, Youssef; Gokcekus, Huseyin; Essayah, Ahmed Mohamed Salah (Engineering, Technology & Applied Science Research, 2023)
The objective of the current paper is to evaluate Lebanon’s wind energy generation potential as an alternative solution to the electricity supply to households and to enhance sustainable technological development. Firstly, the paper aims to investigate the appropriateness of 44 distribution function models for the evaluation of wind speed characteristics and compared them with popular models at 12 locations in Lebanon for the first time. The results showed that Wakeby and Beta distribution functions gave the best fit to the actual data for most locations. Secondly, the techno-economic and environmental feasibility assessment for 10MW grid-connected wind farms was developed based on variations in financial parameters using RETScreen Experts software. The findings demonstrate that the proposed power plant is both technically and financially feasible. It was found that Ain ed Dabaa is the most viable location for the installation of a wind farm.